Rekomendasi Pemilihan Media Tatap Muka Pembelajaran Daring Menggunakan Metode ELECTRE - Elisabeth Y. Yolasb; Lanny Sitanayah; Vivie D. Kumenap (JOINTER : Journal of Informatics Engineering, 2022)
The COVID-19 outbreak that has hit the whole world, including Indonesia, has disrupted community activities, making people in various countries have to stay at home to break the COVID-19 chain. One of the activities affected is the teaching and learning activity. The teaching and learning activity, which should be a face-to-face activity, has to be replaced by using an online system. Due to many existing online learning platforms, it is difficult for educators to determine an appropriate online learning platform or application to support the needs of students. This study proposes a recommendation system, which is built using the Elimination Et Choix Traduisant La Realite (ELECTRE) method, to select an online learning platform. This method is able to process the weight of the value of each criterion and alternative used in order to get the final result in the form of an appropriate alternative. The result of this study is a recommendation system that can assist educators to choose an appropriate online learning platform.